The Poet Ishak Telalović From Livno and His Târih on the Capture of Varad (Prilozi za orijentalnu filologiju, 2017)
The paper brings a poem - a târih - written by the poet Ishak Telalović of Livno on the occasion of the conquest of the Varad Fortress by the Serdar Ali-Pasha 1070 H./l 659/60 A.D. The poem has ten bayts, and each verse - misra’ is a târih which gives the year 1070.With regard to the fact that the author has been almost unknovvn, the event on the occasion of which it was vvritten, and particularly with regard to the way it was vvritten, the poem is a remarkable discovery of high literary achievement in the tarih genre.Along with the facsimile of the original which is kept in the Bosniak Institute in Zürich (No. 142, p. 14b), the paper also brings transliteration of the text in Turkish Latin alphabet, its English translation, and a Chart with nume- rical values of ali the 20 tarihs.